THE NEED FOR INTERNATIONAL COOPERATION IN CRIMINAL MATTERS: CASE OF MADAGASCAR - Saida Tongalaza (Arena Hukum, 2015)
AbstractThe cooperation in criminal matters is a collaboration tool allowing a criminal authority of a country to appeal to a foreign authority for lute against offenses has international character or performance measures within the scope of the criminal proceedings. The internationalization of criminality and other forms of transnational crime were responsible for the implementation of this system at regional and global level. Like all other countries of the world, Madagascar is actively involved in the development of this international cooperation. But one wonders whether the offenses for which such assistance is applied are limited or not. In other words, is that such cooperation is limited to offenses under the International Convention? The answer to these questions requires the determination of the areas on which cooperation can take place. In other words, the statement of offense to the achievement of which assistance or more precisely corporation may be requested. The main Issue on this paper purposing international cooporation between Madagascar as sovereignty state with other states to fight criminal matters. This paper use juridical normative with library research methodology. Madagascar like any other country in the world has signed since its independence, a Judicial Cooperation Agreement to deal with any kind of legal constraint internationally. In fact, the cooperation is a strategy that aims to curb impunity. Therefore: the prerequisite for the establishment of justice. But to achieve effective cooperation, it is necessary that each country shows its resolution to fight together against crime through cooperation.AbstrakKerjasama dalam ranah hukum pidana menjadi alat atau sarana yang memperbolehkan bagi penegak hukum di suatu negara untuk mengajukan banding terhadap negara lain. Keadaan ini harus dipandang sebagai upaya untuk mengikatkan diri dengan tidak dimaksudkan turut campur terhadap proses peradilan pidana. Perbuatan kriminal dalam ruang lingkup internasional dan bentuk lain dari kejahatan trannasional menjadi pemicu dilaksanakannya sistem peradilan pidana ini, baik tingkat regional maupun global. Madagaskar sama halnya dengan negara lain secara aktif turut serta untuk mengembangkan sistem ini, akan tetapi yang menjadi pertimbangan apakah tindakan ini dapat dibatasi atau tidak?. Lain kata apakah tindakan ini dapat dilakukan di bawah Konvensi Internasional?. Jawaban atas pertanyaan ini memerlukan penetapan bagian-bagian dari kerjasama yang diperbolehkan untuk dilakukan. Lain kata pernyataan turut serta dalam ranah kerjasama dapat dicapai melalui permintaan agar dipenuhinya keadaan tersebut. tulisan ini ditujukan untuk mengkaji kerjasama internasional antara Madagascar sebagai sebuah negara berdaulat dengan negara-negara lain dalam memerangi tindak pidana. Tulisan ini menggunakan metode yuridis normatif melalui penelitian kepustakaan (library research). Madagascar memiliki komitmen dalam setiap bidang hukum yang berkaitan dengan kerjasama internasional yang saling mengikat dalam Judicial Cooperation Agreement, demi pencapaian kebutuhan akan keadilan. Kerjasama ini dapat berjalan secara efektif, bila setiap negara memiliki resolusi untuk memerangi kejahatan melalui suatu kerjasama.